The outlet flow structure of vortex chamber with dead end jet actions - Турик, Владимир Николаевич; Милюков, Дмитрий Евгеньевич (Eastern-European Journal of Enterprise Technologies, 2014)
The analysis of the flow structure uniformity in the running (active) part of the vortex chamber in conditions of organizing various control jets, which affect coherent energy-carrying vortex formations in the dead end region of the vortex chamber is conducted. Thermoanemometry data on multiscale outlet flow structure of chamber in the form of distributions of axial and transverse components of the averaged velocity and the corresponding relative intensity of velocity pulsations depending on the control jet parameters is given. The effect of the ratio of working medium flow rate through the control nozzle and at the vortex chamber outlet on the velocity profiles and their pulsations is studied. For the analysis of the flow structure in the active part of the vortex chamber, a new integral parameter - the intensity irregularity degree of velocity pulsations in the exit section is proposed. It is found that the highest values of the integral intensity irregularity degree of axial pulsations are provided by the flow structure control scheme using a coaxial dead end jet, and transversal pulsations - by control scheme using concurrently directed jet with respect to the spiraling energy-carrying vortex formation in the dead-end part of the chamber. The research results are of interest to vortex chamber developers since the obtained profiles of hydrodynamic characteristics of the outlet flows with the investigated jet control schemes indicate the zones of maximum shear effects, so they allow approximately take into account the anisotropy of mass and energy transfer in evaluating the operating modes of chambers with relatively elongated dead end part. These data may be also useful in selecting rational design solutions at the design stage of vortex devices in energy, metallurgical, chemical, aerospace and other industries depending on the purpose of chambers (mixing, separation of media with different densities, the second component supply to the swirling flow and etc.).